Research on the impact of domestic agricultural R&D on high-quality agricultural development in China - Yang, Dandan; Wang, Yongping; Li, Chengjiang; Zhao, Gang; Xu, Fei (Frontiers in Sustainable Food Systems, 2023)
A fresh wave of technical change is seen as one of the most effective ways to achieve sustainable agricultural development due to the declining carrying capacity of resources and the environment. China, a nation with a sizable population, has drawn immense research attention over the following question: How can China promote agricultural transformation and achieve high-quality agricultural development through technological innovation? Based on the panel data that considers 28 provincial-level administrative regions in mainland China from 2010 to 2018, the study utilizes two-way fixed models; thus, it tests the impact of domestic agricultural research and development on high-quality agricultural development. Furthermore, it utilizes the moderating effect to verify the relationship between the two aforementioned factors under the influence of foreign technology introduction, human capital, and financial support. We observed the following: First, the high-quality agricultural development that characterized all the Chinese regions exhibited a steady upward trend. The industrial system, ecological system, and management system exhibited considerable development, whereas the development of the production system was lagging. Second, domestic agricultural research and development has promoted high-quality agricultural development. Third, under the moderating effect of foreign technology introduction, human capital, and financial support, the promotion effect of domestic agricultural research and development on high-quality agricultural development has gradually weakened. This study presents various proposals; thus, it strengthens the role of domestic agricultural research and development in promoting high-quality agricultural development.